Academic and Employment Preferences of Nursing Students at the University of Las Palmas of Gran Canaria: A Cross-Sectional Study - Andrea Ramos-Ramos; Claudio Alberto Rodríguez-Suárez; Candelaria de la Merced Díaz-González; José Verdú-Soriano; Miriam Berenguer-Pérez; Héctor González-de la Torre (Nursing Reports)
Background/Objectives: It is well known that there are differences in the academic and employment preferences of nursing students once they have completed their undergraduate studies in nursing. These preferences are largely influenced by students’ affinity for certain thematic areas over others. Therefore, the objective of this study was to identify the employment and academic preferences of third- and fourth-year Nursing Degree students at the University of Las Palmas de Gran Canaria (ULPGC). Methods: A cross-sectional, descriptive observational study was conducted among nursing students across three campuses of the ULPGC (Canary Islands, Spain). An online questionnaire was used to collect various sociodemographic and academic variables, as well as preferences across ten thematic areas. Descriptive and bivariate inferential analyses were performed, along with a correlation analysis among the areas. Results: The areas of highest preference were “Emergency Nursing”, “General Nursing”, and “Family and Community Nursing”. The areas of lowest preference were “Other Areas (teaching, management, research)”, “Mental Health and Psychiatric Nursing”, and “Geriatric Nursing”. Three clusters of closely correlated areas were identified: cluster 1 (Intensive and Critical Care Nursing, Emergency and Emergency Nursing and Operating Theatre and Anaesthesia Nursing), cluster 2 (Obstetric-Gynaecological Nursing–Midwifery, Paediatric Nursing and Mental Health and Psychiatric Nursing) and cluster 3 (remaining areas). A significant proportion of students expressed intentions to pursue postgraduate studies. Conclusions: Strategies should be implemented to enhance students’ preferences in the areas of “Mental Health and Psychiatric Nursing” and “Geriatric Nursing”, which are areas where there is a high demand for nurses. It is also necessary to increase their interest in research, management, and teaching. This study was not registered.